HUBUNGAN ANTARA PEMAKAIAN LENSA KONTAK DAN RISIKO BLEFAROPTOSIS DIDAPAT - Putri, Febianza Mawaddah (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Objectives: Contact lenses (CL) wear has been reported to be associated with acquired blepharoptosis. This literature review aims to summarize and evaluate the risk of acquired blepharoptosis in contact lens wearers. Methods: Literature searching was conducted using three online databases including PubMed, Cochrane Library, and Embase. Search terms such as “contact lens”, “ptosis”, and “blepharoptosis” were included. Reference lists of each study were also assessed for potentially relevant sources. Results: Using relevant search terms in various databases, a total of three articles were included in this review. All studies reviewed were single-center retrospective studies. The three studies suggested that wearing contact lens was significantly associated with blepharoptosis. Long-term contact lens wear, ranging from 15 to 34 years, seemed to have a significant effect on the incidence of blepharoptosis. Hard contact lens (HCL) wear has a greater risk for ptosis to occur than soft contact lens (SCL) wear. Conclusion: There is evidence of a clear association between hard or soft contact lens wear and an increased risk of blepharoptosis. Patients wearing contact lenses should be informed of the risk of blepharoptosis, and a history of contact lens wear should be sought in all patients who have acquired blepharoptosis.